Market Orientation Small Medium Enterprise: A Bibliometric Analysis of Publications between 1994 and 2023 Using VOSviewer Software - Muhammad Fahmi; Muhammad Andi Prayogi; Muhammad Taufik Lesmana; Maharani Citra Kencana; Syahnita Syahnita (Proceeding International Pelita Bangsa, 2023)
This paper aims To analyze the most prolific and influential articles involved in market orientation research (MO) between 1994 to 2023. This Research paper uses bibliometric analysis techniques, quotations, and cocitations with Vosviewer software for investigated 766 publications in MO from 1994 to 2023 and uses the scopus.com database to visualize relevant articles and their results. Results of the analysis bibliometrics describe evolution research and interests scientific in market orientation over time. Study This gives more understanding _ of the focus of different studies and highlights contributor Main and Network collaboration in it. Second, literature about continued market orientation is growing and diversifying, focusing on understanding concepts and applications in the contemporary business world. While the novelty obtained from the study, This use approach bibliometric with VOSviewer and Scopus.com to analyze development literature about market orientation provides a holistic and in-depth view of relevant literature and provides a base for development understanding and application draft market orientation.